Mauritius: cool marketing from a tropical island - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
AS the visitor to Maurtius drives from the international airport on the south-eastem tip of the island towards the capital Port Louis on the west coast, or past the smart luxury hotels scattered discreetly around the shores, he quickly realizes...